Nomogram for Predicting Overall Survival and Assessing the Survival Benefit of Adjuvant Treatment in pT1-2N0M0 Triple-Negative Breast Cancer: A Surveillance, Epidemiology, and End Results-Based Study - Mao, Qixin; Liu, Shanqing; Lv, Minhao; Sun, Yadong; Zhang, Chongjian; Li, Lianfang (Frontiers in Oncology, 2022)
Background: Accurate survival prediction of triple-negative breast cancer (TNBC) is essential in the decision-making of adjuvant treatment. The aim of this prospective study was to develop a nomogram that predicts overall survival and assists adjuvant treatment formulation. Methods: A total of 16,977 patients with pT1-2N0M0 TNBC between 2010 and 2015 from the SEER database were enrolled. Independent prognostic factors associated with overall survival (OS) were identified using univariate and multivariate Cox regression hazards method and utilized to compose the nomogram. The survival benefit of adjuvant treatment on OS were analyzed after stratification by nomogram sum-score. Results: Patients were randomized 7:3 into the training and validation cohorts. Multivariate analysis revealed that age at diagnosis, grade, tumor size, laterality, and mastectomy type were independent prognostic factors of OS and were integrated to develop a nomogram for predicting prognosis. Patients were stratified into 3 prognostic subgroups according to the sum-score of our nomogram. There were no significant differences found in OS between surgery alone and other adjuvant treatment strategies in low risk group. In moderate risk group, patients receiving chemotherapy or the combination of chemotherapy and radiotherapy showed better OS than those receiving surgery alone or radiotherapy alone. For patients in high risk group, the combination of chemotherapy and radiotherapy could maximally improve the overall survival rate of patients. Conclusion: A novel nomogram for OS prediction and risk stratification in patients with pT1-2N0M0 TNBC was developed. This cohort study reveals the prognostic roles of different adjuvant treatment strategies in subgroups, which may provide a reference for the decision-making of postoperative treatment, eventually improving prognosis for individual patients.